Surviving in Difficult EFL Classroom: Teachers’ Perspectives and Coping Strategies (Journal of NELTA, 2018)
English language teachers often encounter with the situations in which they are faced with defiance, aggression and multiple verbal and physical abuses in their classroom. Moreover, they have pressures of unrealistic expectations and blamed for complex failures of students and the whole system, which makes their survival in difficult classroom even more difficult. So, this is a small-scale research study that investigates EFL teachers’experiences and the perspectives on the difficult classroom situations. The study reveals that teachers are not the only responsible persons for students’ unexpected behaviours; but there are several other reasons to contribute to it. Journal of NELTA, Vol 20 No. 1-2, December 2015 , Page: 16-26